PRESENCIA DE METALPHEUS ROSTRATIPES (Pocock, 1890) (CRUSTACEA: ALPHEIDAE) EN EL CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
Samples of skeletons of the coral Acropora palmata obtained on the reef crest of Isla Grande, Islas del Rosario (colombian Caribbean),were found to contain two  specimens of the family Alpheidae, Metalpheus rostratipes (Pocock, 1890). This shrimp species is reported for the first time from the colombian Caribbean.